2005
DOI: 10.1191/1352458505ms1140oa
|View full text |Cite
|
Sign up to set email alerts
|

Microglial imaging with positron emission tomography and atrophy measurements with magnetic resonance imaging in multiple sclerosis: a correlative study

Abstract: The present study suggests that brain atrophy, correlating with disease duration and disability, is directly related to NAWM and T2-lesional inflammation as measured by microglial activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
89
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 59 publications
1
89
0
1
Order By: Relevance
“…One early study suggested the presence of focal areas of increased uptake in normal-appearing white (and gray) matter (8). However, patterns of ligand uptake in T2-weighted hyperintensities and correlations between 11 C-(R)-PK11195 uptake and disease duration and disability have been inconsistent in previous studies (8,10,33). This inconsistency could reflect differences in patient populations, differences in the proportion of specific (displaceable) signal between 18 F-PBR111 and 11 C-(R)-PK11195, or accurate modeling, which is particularly challenging for the lower-affinity 11 C-(R)-PK11195 (24,34).…”
Section: Discussionmentioning
confidence: 99%
“…One early study suggested the presence of focal areas of increased uptake in normal-appearing white (and gray) matter (8). However, patterns of ligand uptake in T2-weighted hyperintensities and correlations between 11 C-(R)-PK11195 uptake and disease duration and disability have been inconsistent in previous studies (8,10,33). This inconsistency could reflect differences in patient populations, differences in the proportion of specific (displaceable) signal between 18 F-PBR111 and 11 C-(R)-PK11195, or accurate modeling, which is particularly challenging for the lower-affinity 11 C-(R)-PK11195 (24,34).…”
Section: Discussionmentioning
confidence: 99%
“…Both [ 11 C](R)-PK11195 and [ 11 C]PK11195 have been used as positron emmision tomography (PET) tracers to study activated microglia in various neurologic disorders. It has been used to study stroke (Ramsay et al, 1992;Pappata et al, 2000;Gerhard et al, 2000Gerhard et al, , 2005a), Alzheimer's disease (Groom et al, 1995; Cagnin et al, 2001a;Versijpt et al, 2003), multiple sclerosis (Banati et al, 2000;Debruyne et al, 2002Debruyne et al, , 2003Versijpt et al, 2005) and various other diseases (Pappata et al, 1991; Banati et al, 1999Banati et al, , 2001Goerres et al, 2001;Cagnin et al, 2001bCagnin et al, , 2004Cicchetti et al, 2002;Gerhard et al, 2003Gerhard et al, , 2004Gerhard et al, , 2005bTurner et al, 2004Turner et al, , 2005Venneti et al, 2004;Henkel et al, 2004;Ouchi et al, 2005). Most studies have used a reference tissue approach to quantify binding, either by applying the simplified reference tissue model (SRTM) (Lammertsma and Hume, 1996) or by using uptake normalized to a reference region.…”
mentioning
confidence: 99%
“…In the brain, (R)- [ 11 C]PK11195 binds to activated microglia [7] which are part of the brain's immune system. (R)- [ 11 C] PK11195 has been used extensively to image brain inflammation using PET [8][9][10][11][12][13][14][15][16]. Methods have been published regarding the quantification of (R)- [ 11 C] PK11195 binding in the brain [17][18][19].…”
Section: Introductionmentioning
confidence: 99%